SENSITIVITY OF POTATO CULTIVARS TO FOMESAFEN AND METRIBUZIN - Golubev, Artem (Potato Journal, 2022)
The objective of this research was to evaluate the sensitivity of 3 potato cultivars (different ripening periods) to fomesafen (300 g/ha a.i.) and metribuzin (980 g/ha a.i.) herbicides applied preemergence (PRE). The experiments were conducted during 2020 and 2021 in the Leningrad region of the Russian Federation. The application of herbicides at all three potato cultivars caused slight yellowing of tips of the leaves (less than 5%). This symptom of phytotoxicity was more noticeable in the early season cultivars Udacha (ripening time from 65 days) and Nevsky (ripening time from 75 days). The negative effect of herbicides on plant height was demonstrated in arid conditions (in 2021), when after applying fomesafen and metribuzin there was a significant delay in plant growth in two cultivars (Udacha and Avrora) at 7 and 14 days after emergence (DAE). By 28 DAE, the plant height of all three cultivars after herbicide treatments and in the nontreated check were equalized (differences did not exceed 10%). Despite the observed symptoms of phytotoxicity, none of the herbicide treatments in both years didn’t show a statistically significant negative effect of herbicides on potato yield, indicating the high regenerative capacity of potatoes.